Pore structure and fractal characteristics of shale reservoirs in Jurassic Lianggaoshan Formation, northeastern Sichuan Basin - Qi LI; Ruiqian CHEN; Fei SHANG; Ling LI; Xin BAI (Shiyou shiyan dizhi)
The Jurassic Lianggaoshan Formation in the northeastern Sichuan Basin is a key exploration target for shale oil. However, due to limited exploration in this area, the shale reservoir characteristics remain unclear. Experiments such as X-ray diffraction mineral analysis, scanning electron microscopy analysis, high-pressure mercury intrusion, and low-temperature nitrogen adsorption were conducted to systematically study the storage space types and fractal features of the Lianggaoshan Formation shale reservoir. The primary mineral composition of the Lianggaoshan Formation reservoir in the northeastern Sichuan Basin is clay minerals, with an average content of 51.57%, followed by feldspar and quartz minerals at an average of 47.11%, while carbonate minerals are scarce, averaging 2.69%. The dominant storage space types mainly include interlayer pores of clay minerals, intergranular pores between quartz and feldspar, and micro-fractures. The low-temperature nitrogen adsorption curve of the Lianggaoshan Formation shale aligns with type Ⅳ in the classification system of the International Union of Pure and Applied Chemistry, indicating slit-type pores. Based on the morphology of mercury intrusion curves and reservoir physical properties, the reservoir is divided into four types. From type Ⅰ to type Ⅳ, drainage pressure and median pressure increase, whereas maximum mercury saturation decreases, leading to enhanced reservoir heterogeneity. The "FHH"model calculations show that the pore surface fractal dimension (DN1) is greater than the pore structure fractal dimension (DN2), indicating that the pore surface exhibits greater complexity than the internal pore structure. The average fractal dimension D1 of large pores, calculated using the water saturation method, averages 2.991 2, while that of small pores (D2) averages 2.679 2. The larger pores have a fractal dimension closer to 3 and exhibit a more concentrated distribution, indicating that highly heterogeneous large pores contribute more significantly to the reservoir. Correlation analysis shows that there is a correlation between D and the contents of minerals (quartz and clay minerals) as well as pore-throat struture parameters, proving that large pores are the main contributers to the shale reservoir space in the study area. Through qualitative and quantitative analyses, this paper conducts a reservoir evaluation of the Lianggaoshan Formation shale in the northeastern Sichuan Basin, offering insights for the subsequent evaluation and selection of favorable exploration intervals in this area.